Abnormal solute distribution near the eutectic triple point. (May 2019) - Zhang, Ang; Du, Jinglian; Guo, Zhipeng; Wang, Qigui; Xiong, Shoumei
Abstract: Most research into the formation of the lamellar eutectics has focused on the growth patterns. However, those growth patterns can be attributed to the behavior of the triple junction, at which the solute distribution determines the long-range spatial periodicity of patterns. From both theoretical validation and phase-field simulations, we characterize the solute concentration at the triple point and demonstrate the existence of abnormal solute distribution. The solute concentration at the triple point equals the eutectic concentration only when the coexisting solid phases are evenly distributed, which is essential to balance the concentration gradient and maintain the interfacial thermodynamic equilibrium. Graphical abstract: Unlabelled Image